Предмет: Математика,
автор: NikaaVishnya
Упростите выражение:
(х+3)(у-2)+2х-3у+1=
(х-2)(у+5)-5х+2у=
Ответы
Автор ответа:
2
ху-2х+3у-6+2х-3у+1=ху-5. 2)ху+5х-2у-10-5х+2у=ху-10 перемножаем скобки и сокращаем
Автор ответа:
2
(x+3)*(y-2)+2x-3y+1=xy-2x+3y-6+2x-3y+1+xy-5
(x-2)*(y+5)-5x+2y=xy+5x-2y-10-5x+2y=xy-10
(x-2)*(y+5)-5x+2y=xy+5x-2y-10-5x+2y=xy-10
Похожие вопросы
Предмет: Литература,
автор: Аноним
Предмет: Английский язык,
автор: hurtinbogdan
Предмет: Математика,
автор: nutaanna49
Предмет: Информатика,
автор: Dimasivushkin
Предмет: Математика,
автор: sofia251005